2019
DOI: 10.1029/2017ms001245
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Atmosphere‐Fire Simulations of the Black Saturday Kilmore East Wildfires With the Unified Model

Abstract: A model for the spread of a wildfire is developed within the U.K. Met Office Unified Model (UM) and used to simulate the Kilmore East fire complex (in southeastern Australia) on Black Saturday (7 February 2009). The UM is configured with four nests with horizontal grid spacings of 4 km, 1.5 km, 444 m, and 144 m. In the first simulation, the UM simply provides predictions of the near‐surface conditions for the wildfire model with no feedbacks to the atmosphere from the fire. In the second, the atmosphere and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…More extreme cases of spotting are characterised by long distances (up to many kilometres) and/or the ignition of tens or hundreds of spot fires in mass spotting events [10,11]. Interaction between multiple spot fires and the source fire potentially increases burning intensity, flame heights [12], and wildfire spread rates over large areas [11,13]. Such interactions are likely to depend on the distribution of spot fires (number and distances); for example, multiple spot fires in close proximity (to the source fire and/or other spot fires) are likely to interact, whereas isolated spot fires are not.…”
Section: Introductionmentioning
confidence: 99%
“…More extreme cases of spotting are characterised by long distances (up to many kilometres) and/or the ignition of tens or hundreds of spot fires in mass spotting events [10,11]. Interaction between multiple spot fires and the source fire potentially increases burning intensity, flame heights [12], and wildfire spread rates over large areas [11,13]. Such interactions are likely to depend on the distribution of spot fires (number and distances); for example, multiple spot fires in close proximity (to the source fire and/or other spot fires) are likely to interact, whereas isolated spot fires are not.…”
Section: Introductionmentioning
confidence: 99%
“…Although infrared video from that fire suggests lee slope rotors may not have formed, the high numbers of spot fires that merged resulted in a similar effect to that of our hill present experiments. Moreover, coupled modelling by Toivanen, Engel [ 38 ] found that the spread of the Kilmore East wildfire in 2009 (Victoria, Australia) could be reproduced only if the ignition and merging of 18 downwind spot fires was incorporated. These suggest that, considering the combined ROS, spotting and merging might be important not just over a single slope (as in our experiments), but over a much larger scale (spotting occurred up to 30 km away in the Kilmore East wildfire [ 1 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The Kilmore East Black Saturday simulations [26] and simulations in the progress of the Waroona and Sir Ivan fires show the potential value of the system. Numerous development steps would be required for operational use, including the inclusion of fuel grids compatible with the AFDRS, variable fuel moisture and the inclusion of smoke transport.…”
Section: Access-firementioning
confidence: 94%
“…The operational atmospheric grids of 1.5 km can be downscaled to 400-100 m, which is an appropriate spatial scale for the simulation of landscape-scale fires. Sensitivity tests run with both ACCESS-Fire [26] and CAWFE [31] showed limited improvement in CFA simulation results when the resolution on the inner nest was varied from 400 m to 100 m.…”
Section: Scalabilitymentioning
confidence: 98%
See 1 more Smart Citation